Effects of total head and solar radiation on the performance of solar water pumping system. (April 2018) - Tiwari, Arunendra K.; Kalamkar, Vilas R.
Abstract: The solar photovoltaic water pumping system (SPVWPS) is increasingly popular in non-electrified population in fulfilling the irrigation and drinking water demand. It can be a potential option than conventional pumps to draw down water in developing countries like India. However, to gain wider acceptance, scientific information and results are needed with the system installation and sizing. In this study, the performance of SPVWPS is investigated with helical rotor pump. The effect of solar radiation and total head on water output of SPVWPS has been analyzed with the optimized PV array configuration. Four pumping head have been analyzed (4 bar, 6 bar, 8 bar and 10 bar). The experiments have been performed for various heads on clear sunny daylight hours in an artificial well at VNIT campus Nagpur (India). The effect of variation of radiation on the performance of pump has also been studied. The best system efficiency is founded for the total head of 10 bar which is suggested for helical rotor submersible pump. Also, for Nagpur (India), the system should be sized as per the irradiance range 400–800 W/m 2, as more than 60% of the total solar energy falls in this range. Highlights: An experimental study of SPVWPS is carried out using optimized PV array. Detailed analysis of total head and solar radiation variations on water output. Performance analysis of SPVWPS in terms of subsystem efficiency and flow rate.